“ISLAMISASI SAINS DAN SAINTIFIKASI ISLAM”: MODEL MANAJEMEN PEMBERDAYAAN DI MASJID SALMAN ITB BANDUNG - Anik Farida (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
This paper discusses part of the findings of a larger study entitled “The Effectiveness of Mosque Management in the Empowerment of People.” It specifically looks at the case of the Salman Mosque of ITB in Bandung. This research finds that the Salman Mosque is a place of knowledge empowerment in the area of Islamic Science and Technology, looking at science and technology from an Islamic perspective. The teachings of its mosque has led to changes in the mindsets, perspectives, worldviews and paradigms of the target audience, students. Ultimately, this religious empowerment model has led students—the countrys future scientists and technocrats—to value nature. It has taught them not to exploit nature, as practiced in secular science and technology, but to be khalifah fil-ardhi, protectors of nature.